A Review on the Low-Dimensional and Hybridized Nanostructured Diamond Films. (25th October 2015) - Li, Hongdong; Cheng, Shaoheng; Li, Jia; Song, Jie
Abstract : In the last decade, besides the breakthrough of high-rate growth of chemical vapor deposited single-crystal diamonds, numerous nanostructured diamond films have been rapidly developed in the research fields of the diamond-based sciences and industrial applications. The low-dimensional diamonds of two-dimensional atomic-thick nanofilms and nanostructural diamond on the surface of bulk diamond films have been theoretically and experimentally investigated. In addition, the diamond-related hybrid nanostructures of n-type oxide/p-type diamond and n-type nitride/p-type diamond, having high performance physical and chemical properties, are proposed for further applications. In this review, we first briefly introduce the three categories of diamond nanostructures and then outline the current advances in these topics, including their design, fabrication, characterization, and properties. Finally, we address the remaining challenges in the research field and the future activities.